The Composition and Distribution of Household Wealth in Indonesia - Thomas Soseco (Universitas Negeri Malang, 2018)
As a developing country, Indonesia still suffers from inequality among classes. This inequality is reflected from unequal distribution in wealth owned by households. Thus, the descriptive information related to household wealth is an initial attempt to examine the composition and distribution of household wealth in Indonesia. This is a descriptive research, employing information from Indonesian Family Life Survey (IFLS) wave 5. The focus in this research is mean, median, and distribution of wealth components seen from age groups and quantiles perspectives. The results of this research are: (1) household wealth in Indonesia is unequally distributed. Even though the mean of total wealth is 147 million rupiah, but the middle household (median) receive 56.8 million rupiah. (2) The 10th decile is the wealthiest social class, with wealth more than 500 times bigger than the 1st decile. (3) From age group perspective, the 30-44 years old age group is the wealthiest. (4) There is the existence of negative net wealth. The negative net wealth required further action that cannot easily approached by the descriptive method. Keywords: household wealth, wealth distribution, negative wealthJEL Classification: D31; E01; E21; R20